Linked Lives: Exploring the Narratives of Second-Generation Migrants in Nepal - Devkota, Chhabilal; Dahal, Sanjeev (Molung Educational Frontier, 2021)
This article describes the narratives of second-generation migrants in Nepal. The paper explores the reasons for migration as shared with their offspring by first-generation migrants. The article also shares the narratives by second-generation migrants on experiences of family, school, community, and the State. Second-generation migrants or adult offspring of first-generation migrants from Tibet and India comprised the sampling frame for the qualitative study. Data were collected through a non-probability sampling technique, and in-depth semi-structured interview schedules were used. Nine in-depth interviews were conducted for the study. Thematic analysis was employed to examine the data. Key reasons to migrate to Nepal featured in the narratives of the migrants were opportunities for business, availability of good education, and a suitable climate in Nepal. Furthermore, lack of opportunities for employment and education and instances of violence at their place of origin pushed the migrants towards Nepal. Most of the interviewees shared having solid bonds with their families. They shared mixed experiences (both encouraging and humiliating) at school and varied experiences in their interaction with the broader society (both supportive and conflicting). Furthermore, all interviewees shared challenges in dealing with or receiving help from the Nepali State.